2001
DOI: 10.1099/00221287-147-2-473
|View full text |Cite
|
Sign up to set email alerts
|

A purF mutant of Mycobacterium smegmatis has impaired survival during oxygen-starved stationary phase The GenBank accession number for the sequence reported in this paper is AJ278609.

Abstract: In this study it was demonstrated that a range of transposon mutants of Mycobacterium smegmatis, previously described as having impaired survival in carbon-starved stationary phase, were not markedly affected in O 2 -starved stationary-phase survival. One exception was 329B, a purine auxotroph, which showed a precipitous reduction in viability from 10 8 to 10 3 c.f.u. ml N1 during the first 5-10 d in O 2 -starved stationary phase. This was followed by an equally rapid recovery in culturability to a level withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…4). It has been shown previously that these mutants lose culturability in stationary phase after growth under oxygen-limited conditions (Keer et al, 2001;O'Toole et al, 2003). This behaviour was reproduced in the present study (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…4). It has been shown previously that these mutants lose culturability in stationary phase after growth under oxygen-limited conditions (Keer et al, 2001;O'Toole et al, 2003). This behaviour was reproduced in the present study (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Two possible explanations have been proposed to explain the recovery in viability of purF and devR mutants of Myc. smegmatis: (a) resuscitation of NC cells and (b) regrowth of surviving cells (Keer et al, 2001;O'Toole et al, 2003). The present study, in which MPN conditions were employed, confirms the first possibility.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, Keer et al (2000) have found that several mutants of Mycobacterium smegmatis, defective in stationary phase survival under aerobic or anaerobic conditions, revealed a transient decrease in viability followed by an increase in culturability. The authors suggest at least two possible explanations for this effect : (a) re-growth (cryptic growth) of viable cells, and (b) formation of ' non-culturable ' (and possibly dormant) bacteria in stationary phase and their subsequent resuscitation (Keer et al, 2000(Keer et al, , 2001. Since the authors did not measure culturability by MPN counts, direct evidence was neither sought nor obtained for resuscitation of non-culturable cells.…”
Section: Discussionmentioning
confidence: 99%